Pengenalan dan Pelatihan Laporan Keuangan pada Warga Jl. Merawan 14a Rt. 29 Rw.07 Sawah Lebar Kecamatan Ratu Agung Kota Bengkulu - Ida Ayu Made Er Meytha Gayatri; Wagini Wagini; Tito Irwanto; Tri Febrina; Nia Indriasari (Jurnal Dehasen Untuk Negeri, 2022)
A financial report is a record of a company's financial information within a certain period that can be used to describe the company's performance situation. The benefit of financial statements is to provide information on financial conditions and developments related to individuals or organizations/companies that are taken into consideration for making appropriate and accurate decisions, providing useful information for company management. Residents of RT. 29 RW.07 Sawah Lebar Bengkulu consists of 60 families where most of them work as entrepreneurs, civil servants and construction workers. Residents of RT.29 RW. 07 consists of women who formed an organization called Dasa Wisma RT.29. Seeing the reality on the ground, the need and urgency of the DasaWisma women for skills in making financial reports, it is felt that there is a need for introduction and training in making simple financial reports for RT mothers. 29 RW. 07 in order to improve competence and understanding of the procedures for making simple financial reports, which in the end it is hoped that women will be able to make financial reports independently. To promote understanding of financial reporting assistance and training for women in RT 29 RW.07 Sawah Lebar Bengkulu, it was given by holding lectures on the basics of making financial reports, practicing how to make good financial reports for operational activities, investment activities. , financial and financing activities and initial cash balances and ending cash balances assisted by students and lecturers so that the training materials are on target.